Cyber Counseling Sebagai Metode Meningkatkan Layanan Bimbingan dan Konseling di Sekolah: Literature Review - Lambause, Hasan; tiadi, anggi (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Tompotika Luwuk, 2025)
Internet users are growing rapidly due to advances in information and communication technology. Almost all people in the world use the internet in their daily life. The development of technology also affects the provision of guidance and counseling services, especially in schools. In this era of globalization, online counseling services or cyber counseling are very much needed by counselors or counseling teachers because they can provide services without distance and time limitations. This study aims to discuss the application of cyber counseling in schools. This research uses literature review or literature study in the form of journal articles. The results showed that cyber services are not effective because they can provide benefits for counselors and students to conduct counseling that is not limited to distance and time. Several methods are used to conduct online counseling, including: via email, Facebook, asynchronous chat, real applications, video conferencing, cell phones, and websites. Counseling teachers and Keywords: Cyber Counseling, Counseling Guidance Services, Schools.